Evaluasi Kualitas Website Pemerintah Daerah Dengan Menggunakan Webqual 4.0 dan Importance Performance Analysis (IPA) (Studi Kasus Dinas Kebudayaan dan Pariwisata Kabupaten Pasuruan) - Ilham Febi Muzacki; Andi Reza Perdanakusuma; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The role of the website for a governmental institution nowadays has become an important part of its institution, including the Pasuruan Regency Culture and Tourism Department. However, the website of the Culture and Tourism Department of Pasuruan Regency has never been evaluated since it is officially published on 2016, so that the Pasuruan Regency Culture and Tourism Department does not know the quality of its website. This study analyzed and measured the service quality of the Pasuruan Regency Culture and Tourism Office's websiter based on the user's point of view. User data is obtained by distributing questionnaires based on 3 dimensions in webqual 4.0, namely usability dimensions, information and service interaction. Then, the results of the questionnaire were analyzed using the Importance Performance Analysis (IPA) method. The results of the analysis showed that the website of the Culture and Tourism Office of Pasuruan Regency is not in line with the expectations of users with the results of conformity analysis of 95.79% or <100% and the average analysis of the gap is -0.13 or <0. Priority improvements on this website were in the attribute of number 14 (website of the Culture and Tourism Department of Pasuruan Regency has provide detailed information) and 20 (website of the Culture and Tourism Department of Pasuruan Regency make it easy to communicate with the officer) which are attribute of quadrant A. Recommendations are given is an improvement on the attribute in quadrant A.